Proteolytic cleavage of elafin by 20S proteasome may contribute to inflammation in acute lung injury. Issue 4 (14th December 2012) - Kerrin, Aoife; Weldon, Sinéad; Chung, Allen Hung-Kang; Craig, Thelma; Simpson, A John; O'Kane, Cecilia M; McAuley, Danny Francis; Taggart, Clifford C
Abstract : Rationale: We hypothesise that elafin levels in acute lung injury (ALI) decrease over time due, in part, to proteolytic degradation as observed in other lung diseases. Objectives: The aim of this study was to characterise temporal changes in elafin concentration in patients with ALI and to evaluate whether a decrease in elafin levels is due to elevated protease activity. Methods: Bronchoalveolar lavage fluid (BALF) was obtained from patients with ALI within 48 h of onset of ALI (day 0), at day 3 and at day 7. Elafin levels were quantified by ELISA. Elafin susceptibility to proteolytic cleavage by ALI BALF was assessed by Western blot and by high-performance liquid chromatography–mass spectrometry. Measurements and main results: Elafin levels were found to be significantly increased at the onset of ALI compared with healthy volunteers and fell significantly by day 7 compared with day 0. In contrast, levels of secretory leukocyte protease inhibitor did not decrease over time. This decrease in elafin was due to cleavage by the 20S proteasome which was significantly increased in ALI BALF. Incubation of ALI BALF with the proteasome inhibitor epoxomicin confirmed that 20S proteasome protease activity was responsible for proteolytic cleavage of elafin, resulting in diminished anti-elastase activity. In addition, free neutrophil elastase activity significantly increased in ALI BALF from day 0 to day 7. Conclusions: Elafin concentrations fall within the pulmonary compartment over the course of ALI as a result of proteolytic degradation. This loss of elafin may predispose people, in part, to excessive inflammation in ALI.